Consumer knowledge and attitudes toward healthy eating in Croatia: a cross-sectional study - Ljubičić, Marija (2017)
Unlike fast and restaurant food, diet rich in fibre is known to contribute significantly to health. The aim of our study was to assess eating habits such as consumption of fibre-rich, fast, and restaurant food of the general population in Croatia. For this purpose we used a validated survey designed by the Polytechnic Institute Viseu in Portugal, which includes questions about demographics, good eating habits related to the consumption of the main sources of dietary fibre (fruit, vegetables, and whole grains), and unhealthy eating habits related to the consumption of fast food and restaurant meals. Between October 2014 and March 2015 we received answers from 2,536 respondents aged between 18-70 years, of whom 67.4 % were women and 32.6 % were men. Most respondents reported consuming one serving of vegetables and one piece of fruit a day, and whole grains every other day. Women and urban residents reported consuming larger amounts of fruit, vegetables, and whole grains than men (p<0.001). Men, in turn, reported eating out and eating fast food more often than women (p<0.001). Eating out highly correlated with eating fast food, which translates to lower consumption of dietary fibre (p<0.001). Higher education correlated positively with the consumption of fibre-rich food, but it also correlated positively with the consumption of fast and restaurant food (p<0.001). While eating fast food is not the predominant dietary practice in Croatia, over 50 % of respondents have reported eating fast food at least once a week. Our data also indicate that consumption of fruit, vegetables, and whole grains falls below the national and international dietary recommendations.